Water characteristic curve for soils in Kazakhstan - Satyanaga, A. (2024)
Flux boundary conditions must always be taken into account when analyzing soil behavior under climatic conditions. Since environmental conditions are constantly changing, it is difficult to predict the expansive behavior of the soil and work with it. The soil-water characteristic curve (SWCC) of soils is one of the most important indicators that carries information on the interaction of the air, liquid, and solid phases of soils. Even though large databases of various soil characteristics have now been created in Kazakhstan, many territories remain unexplored with the construction of the main soil-water characteristics curve since the study and construction of these functions can take a long time. The main objective of this study is to construct the SWCC for various soil types throughout Kazakhstan. To achieve it, soil data were collected from the available geotechnical investigations to draw up the soil profile and its properties in the studied regions. The results of the analyses indicate that soils in Kazakhstan can be divided into three main regions. The typical SWCC for different soil classifications at different regions is generated as a result from this study.